Seismic isolation in buildings to be a practical reality: behavior of structure and installation technique - Islam, A.; Jameel, M.; Jumaat, Mohd Zamin (J. Eng. Technol. Res, 2011)
Although a great deal of research has been carried out regarding seismic isolation, there is a lack of proper research on its behavior and implementing technique in low to medium seismic region. The basic intention of seismic protection systems is to decouple the building structure from the damaging components of the earthquake input motion, that is, to prevent the superstructure of the building from absorbing the earthquake energy. This paper reviews a number of articles on base isolation incorporation in building structure. Lead rubber bearing (LRB), high damping rubber bearing (HDRB), friction pendulum system (FPS) have been critically explored. This study also addressed the detail cram on isolation system, properties, characteristics of various device categories, recognition along with its effect on building structures. Meticulous schoolwork has also been accomplished about installation technique for various site stipulations. The entire superstructure is supported on discrete isolators whose dynamic characteristics are chosen to uncouple the ground motion. Displacement and yielding are concentrated at the level of the isolation devices, and the superstructure behaves very much like a rigid body. Rigorous reckoning illustrated the isolation system as very innovative and suitable in buildings to withstand the seismic lateral forces and also contributed to safety ensuring flexibility of structures.